PRIVATIZATION OF STATE OWNED ENTERPRISES IN RELATION WITH GOLDEN SHARE OWNERSHIP BY STATE IN ORDER TO SUPPORT INDONESIAN ECONOMIC DEVELOPMENT - Nyulistiowati Suryanti (Indonesian Journal of Dialectics, 2011)
The decision to implement the privatization of State Owned Enterprises (SOEs) in Indonesia was essentially due to the circumstances that they are not considered self-reliant and not perform, and therefore privatization is an alternative course of action to reform SOEs.  The privatization of the SOEs, however, raises the question whether the private management of SOEs as a business entity can still preserve the public interests.  Based on the abovementioned arguments, the purpose of this  research are:  first, to formulate the state’s management strategies based on company law in order to enhance the role of SOE’s as a mainstay of Indonesia's economic development; second, to formulate the function of golden shares in the privatized SOEs and its implication with the principle of justice in developing the Indonesian economy; and third, to formulate the regulatory privatization perspective of the SOEs as the driver of Indonesia’s economic development in realizing the aspiration of a welfare state.         This research  uses a normative juridical approach, namely to assess and examine logically the legal aspects of the underlying strategy of SOE management and their application in-concreto.  Therefore, the specification of the research is descriptive analytic.  In this study the principal data is the secondary data, while the primary data obtained are employed as supporting the secondary data.  Subsequently, research data were analyzed qualitatively.Based on the analysis and deliberation, the obtained conclusions are as follows: First, the SOE's role as a mainstay of Indonesia's economic development  has not been implemented as expected due to the existence of the various provision in the Act of SOE’s that give multi-interpretation in the management of SOE’s. Therefore the role of the SOE’s, so as to support Indonesia’s economic development, has not optimally achieved. Second, the function of the golden share  has yet to fulfill a sense of justice to the community as stated in Article 33 paragraph (2) and (3) of the 1945 Constitution fourth Amendment during the privatization of SOE’s because it has not being used in accordance with its intention.  Third, the government must strictly regulate the privatized shares of  not more than 49 %.